Knowledge and attitude about relining of complete dentures in clinical practice: A cross-sectional study - Akhil Rathi; Rajlakshmi Banerjee; Usha Radke; Seema Lahoti; Shraddha Sahni (Wolters Kluwer Medknow Publications, 2018)
Background: Residual ridge resorption is crucial sequelae of tooth loss. Complete dentures are the most common way of rehabilitating edentulous patients. However, with continuing residual ridge resorption, dentures tend to become loose and unstable causing discomfort, chewing disability, and speech problems. Denture relining is an economical means of improving a denture's stability and retention. An understanding of the clinical indications and limitations of these materials and procedures is crucial for clinical success. Aim and Objective: The purpose of this survey was to assess knowledge, attitude, and practice in relining dentures among dental practitioners. Materials and Methods: The cross-sectional survey was conducted using a validated questionnaire on 200 (n = 200) dental practitioners in Nagpur city, Maharashtra. Data analysis was done using proportion test with SPSS EPI INFO software. Results: Although all 200 practitioners were aware of the relining procedure and were routinely carrying out the procedure in their dental clinics, 50% of the practitioners were unaware of the correct relining step by step procedure and were also not sure about the antimicrobial properties of the relining material available in the market. Conclusion: Awareness and scientific knowledge about the relining materials and procedure should be enhanced within general dental practitioners through CDE program and workshops. Steps should be taken to include relining procedure as a part of undergraduate clinical curriculum as well as internship program.